Staphylococcal Arthritis in A White-Tailed Deer (Odocoileus virginianus) - Sikes, Dennis (1968)
A five and one-half year old deer (Odocoileus virginianus) developed an ankylosing periarticular hypertrophic arthritis due to a coagulase positive staphylococcus infection. Complete encasement of the tibio-tarsal (hock) joints with a hypertrophic, and porous osseous mass had occurred with complete loss of articular cartilage. The pathologic alterations of the tissues are compared to those occurring in swine due to Erysipelothrix insidiosa infection which produces a rheumatoid-like arthritis.